A COMPARATIVE STUDY OF FINANCIAL PERFORMANCE IN PT PHAPROS TBK BEFORE AND AFTER INITIAL PUBLIC OFFERING - Fathin, Khusnun; Murtini, Sri; Ayundyayasti, Prima; Raharjanti, Rani (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
The decision to Go Public has a great influence in enhancing the company”™s performance particularly the company”™s financial performance. The purpose of this research is to test whether there are significant differences in the financial performance of PT Phapros Tbk before and after going public through financial ratios. The financial ratios used are Current Ratio (CR), Quick Ratio (QR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Investment (ROI), Return on Equity (ROE), Total Asset Turnover (TATO), and Fixed Asset Turnover (FATO). The population of this research is the financial statements of PT Phapros Tbk, while the sample used is the financial statements for the 2016-2021 period. The data analysis technique used is ratio analysis and then quantitative analysis using the IBM SPSS version 26 application, the tests carried out include descriptive statistical analysis, normality testing, and hypothesis testing. The results of this research state that the financial performance of Current Ratio (CR), Quick Ratio (QR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Investment (ROI), Return on Equity (ROE), and Total Asset Turnover (TATO) have significant difference between before and after going public. While the financial performance of Fixed Asset Turnover (FATO) did not have a significant difference after going public.